Graphitic materials, methods of making and applications
Patent Information
- Application Number
- CN202610979135.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-09-29
- Estimated Expiration
- 2046-07-02
AI Technical Summary
此外,现有制备方法多依赖经验调整,缺乏有效的性能评价与筛选指标,致使不同批次产品的光学与结构性能一致性差,可重复性低,难以满足高端晶圆制造对耗材稳定性、均一性及规模化量产的要求
本发明提供的石墨材料保持光固系数为0.03-0.15cm3/g,通过光固系数将石墨材料的光学响应能力与结构承载能力平衡,即保证单位质量材料对光的有效透过行为稳定可控,有利于石墨材料具备稳定的光传输特性;同时还具有较高的批次一致性。
Smart Images

Figure CN122482813B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of consumables technology for wafer manufacturing, and more specifically, to graphite materials, preparation methods, and applications. Background Technology
[0002] In wafer fabrication, graphite materials are frequently used as load-bearing or auxiliary structural components, especially in critical processes such as photopolymerization and cleaning. Their optical response characteristics (particularly their transmittance at specific wavelengths) significantly impact process stability and product yield. Current research on graphite materials largely focuses on mechanical strength, electrical and thermal conductivity, or purification grade, neglecting the coupling relationship between their optical behavior in the deep ultraviolet band (e.g., around 260 nm) and their microstructure (porosity, density). Furthermore, existing preparation methods rely heavily on empirical adjustments, lacking effective performance evaluation and screening indicators. This results in poor consistency in optical and structural performance across different batches, low repeatability, and difficulty in meeting the requirements of high-end wafer manufacturing for material stability, uniformity, and large-scale mass production.
[0003] Therefore, developing a graphite material with stable optical transmission characteristics, good batch consistency, and the ability to effectively balance optical response and structural load-bearing capacity, as well as corresponding preparation and screening methods, is a technical problem that urgently needs to be solved in this field.
[0004] In view of this, the present invention is proposed. Summary of the Invention
[0005] The purpose of this invention is to provide graphite materials, preparation methods and applications, and to provide a graphite material with a suitable optical curing coefficient.
[0006] This invention is implemented as follows: In a first aspect, the present invention provides a graphite material, wherein the optical curvature coefficient of the graphite material is 0.03-0.15 cm⁻¹. 3 / g, where the optical solidification coefficient = transmittance at 260nm wavelength × porosity / density.
[0007] In an optional embodiment, the optical curvature of the graphite material is 0.04-0.12 cm⁻¹. 3 / g.
[0008] In an optional embodiment, the optical curvature of the graphite material is 0.04-0.05 cm⁻¹. 3 / g.
[0009] In an optional embodiment, the optical curvature of the graphite material is 0.05-0.07 cm⁻¹. 3 / g.
[0010] In an optional embodiment, the optical curvature of the graphite material is 0.10-0.12 cm⁻¹. 3 / g.
[0011] Secondly, the present invention provides a method for preparing the graphite material according to any one of the foregoing embodiments, comprising: The raw material mixture is cold-pressed to obtain the initial product; The initial product is subjected to heat treatment, carbonization, and graphitization in sequence to obtain the graphite material.
[0012] In an optional embodiment, the raw material mixture comprises the following components by weight: 100 parts of pitch coke, 10-12 parts of microcrystalline wax powder, 5-7 parts of nano-sized hollow carbon spheres (20-500 nm, Xi'an Qiyue Biotechnology), and 10-20 parts of phenolic resin.
[0013] Thirdly, the present invention provides a method for preparing graphite material according to the foregoing embodiments, wherein the cold pressing pressure is 15-35 MPa; And / or, the heat treatment includes heating the primary product to 138-142°C at 7-9°C / min and holding it at that temperature for 4-6 hours, and then cooling it to 18-30°C; And / or, the carbonization includes: using an inert gas as a protective gas, heating the heat-treated primary product to 315-325℃ at 0.5-0.7℃ / min and holding it at that temperature for 2-4 hours; then heating it to 375-385℃ at 0.6-0.8℃ / min and holding it at that temperature for 2-4 hours; finally heating it to 1150-1250℃ at 0.6-0.8℃ / min and holding it at that temperature for 9-11 hours to obtain the carbonized crude product; And / or, the graphitization process includes: using an inert gas as a protective gas, heating the carbonized primary product to 2250-2350℃ at a rate of 1.4-1.6℃ / min and holding it at that temperature for 48-60 hours.
[0014] Fourthly, the present invention provides a consumable for wafer manufacturing, comprising the graphite material described in any one of the foregoing embodiments.
[0015] Fifthly, the present invention provides a method for screening graphite material consumables for wafer manufacturing, wherein the graphite material has a photocurability coefficient of 0.03-0.15 cm⁻¹. 3 If the graphite material is / g, then it is a qualified graphite material consumable for wafer manufacturing; the optical curvature coefficient of the graphite material is less than 0.03 cm⁻¹. 3 / g or greater than 0.15cm 3 If / g, then the graphite material is a substandard graphite material consumable for wafer manufacturing; wherein, the optical solidity coefficient = transmittance at a wavelength of 260nm × porosity / density.
[0016] The present invention has the following beneficial effects: The graphite material provided by this invention maintains a light-curing coefficient of 0.03-0.15 cm⁻¹. 3 / g, through the optical-solid coefficient, balances the optical response capability and structural load-bearing capability of graphite materials, that is, ensures that the effective light transmission behavior of a unit mass of material is stable and controllable, which is conducive to graphite materials having stable light transmission characteristics; at the same time, it also has high batch consistency. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 This is a SEM image of the graphite material prepared in Example 1 of this application. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0020] This invention provides a graphite material with a light curing coefficient of 0.03-0.15 cm⁻¹. 3 / g, for example 0.03 cm³ / g, 0.04 cm³ / g, 0.05 cm³ / g, 0.06 cm³ / g, 0.07 cm³ / g, 0.08 cm³ / g, 0.09 cm³ / g, 0.10 cm³ / g, 0.11 cm³ / g, 0.12 cm³ / g, 0.13 cm³ / g, 0.14 cm³ / g, 0.15 cm³ / g, wherein the optical-fixing coefficient = transmittance at a wavelength of 260nm × porosity / density.
[0021] The graphite material of this application balances the optical response capability and structural load-bearing capacity of the graphite material through the optical curing coefficient, which ensures that the effective light transmission behavior of a unit mass of material is stable and controllable. This is conducive to the graphite material having stable light transmission characteristics and can avoid problems such as uneven exposure energy, mismatch of curing crosslinking gradient, and differences in the efficiency of cleaning free radical generation caused by light transmission fluctuations of graphite material. At the same time, it has good batch consistency.
[0022] In an optional embodiment, the transmittance of the graphite material at a wavelength of 260 nm is 0.08-0.18.
[0023] In an optional embodiment, the transmittance of the graphite material at a wavelength of 260 nm is less than 0.08.
[0024] In an optional embodiment, the transmittance of the graphite material at a wavelength of 260 nm is greater than 0.18.
[0025] In an optional embodiment, the porosity of the graphite material is 0.3-0.6.
[0026] In an optional embodiment, the porosity of the graphite material is less than 0.3.
[0027] In an optional embodiment, the porosity of the graphite material is greater than 0.6.
[0028] In an optional embodiment, the density of the graphite material is 0.1-1.0 g / cm³.
[0029] In an optional embodiment, the density of the graphite material is less than 0.1 g / cm³.
[0030] In an optional embodiment, the density of the graphite material is greater than 1.0 g / cm³.
[0031] The present invention also provides a method for preparing the graphite material described in any one of the foregoing embodiments, comprising: The raw material mixture is cold-pressed to obtain the initial product; The initial product is subjected to heat treatment, carbonization, and graphitization in sequence to obtain the graphite material.
[0032] In an optional embodiment, the raw material mixture comprises the following components by weight: The amount of pitch coke is 100 parts; The microcrystalline wax powder is in quantities of 10-12 parts, such as 10 parts, 10.2 parts, 10.4 parts, 10.6 parts, 10.8 parts, 11 parts, 11.2 parts, 11.4 parts, 11.6 parts, 11.8 parts, and 12 parts. Nanoscale hollow carbon spheres (20-500 nm, Xi'an Qiyue Biotechnology) are available in 5-7 parts, for example, 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, 6 parts, 6.2 parts, 6.4 parts, 6.6 parts, 6.8 parts, and 7 parts. The amount of phenolic resin is 10-20 parts, for example, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, or 20 parts.
[0033] This application presents a graphite material using pitch coke as a matrix, microcrystalline wax powder as a homogenizing agent, and nano-sized hollow carbon spheres as a structure-guiding and pore-size-regulating component. Combined with phenolic resin bonding and molding, it forms a graphite structure with good connectivity, uniform pore size, and high skeletal strength. This allows the material to maintain suitable porosity while possessing excellent structural stability, avoiding the defects of traditional graphite such as uneven pore size, numerous closed pores, and high light scattering. This is beneficial for achieving an optical curvature coefficient of 0.03-0.15 cm⁻¹. 3 Graphite materials with high consistency within the range of / g.
[0034] The present invention also provides a method for preparing graphite material according to the foregoing embodiments, wherein the cold pressing pressure is 15-35 MPa, for example 15 MPa, 17 MPa, 19 MPa, 21 MPa, 23 MPa, 25 MPa, 27 MPa, 29 MPa, 31 MPa, 33 MPa, 35 MPa; And / or, the heat treatment includes heating the primary product to 138-142°C at 7-9°C / min and holding it at that temperature for 4-6 hours, and then cooling it to 18-30°C; For example, the heating rate in the heat treatment step can be 7℃ / min, 7.2℃ / min, 7.4℃ / min, 7.6℃ / min, 7.8℃ / min, 8℃ / min, 8.2℃ / min, 8.4℃ / min, 8.6℃ / min, 8.8℃ / min, or 9℃ / min.
[0035] For example, the isothermal temperature in the heat treatment step can be 138℃, 138.4℃, 138.8℃, 139.2℃, 139.6℃, 140℃, 140.4℃, 140.8℃, 141.2℃, 141.6℃, or 142℃.
[0036] For example, the isothermal time in the heat treatment step can be 4 h, 4.2 h, 4.4 h, 4.6 h, 4.8 h, 5.0 h, 5.2 h, 5.4 h, 5.6 h, 5.8 h, or 6 h.
[0037] And / or, the carbonization includes: using an inert gas as a protective gas, heating the heat-treated primary product to 315-325℃ at 0.5-0.7℃ / min and holding it at that temperature for 2-4 hours; then heating it to 375-385℃ at 0.6-0.8℃ / min and holding it at that temperature for 2-4 hours; finally heating it to 1150-1250℃ at 0.6-0.8℃ / min and holding it at that temperature for 9-11 hours to obtain the carbonized crude product; the multi-stage slow heating method in the carbonization step helps to avoid the problems of green body cracking, structural collapse, and performance drift caused by rapid heating, and helps to improve the consistency of density, porosity, transmittance at 260nm wavelength, optical solidity coefficient, etc. of each batch of products.
[0038] For example, the heating rate in the first stage of the carbonization step can be 0.5℃ / min, 0.52℃ / min, 0.54℃ / min, 0.56℃ / min, 0.58℃ / min, 0.6℃ / min, 0.62℃ / min, 0.64℃ / min, 0.66℃ / min, 0.68℃ / min, or 0.7℃ / min.
[0039] For example, the first stage of constant temperature in the carbonization step can be 315℃, 316℃, 317℃, 318℃, 319℃, 320℃, 321℃, 322℃, 323℃, 324℃, or 325℃.
[0040] For example, the first isothermal time in the carbonization step can be 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3.0 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h, or 4 h.
[0041] For example, the second heating rate in the carbonization step can be 0.6℃ / min, 0.62℃ / min, 0.64℃ / min, 0.66℃ / min, 0.68℃ / min, 0.7℃ / min, 0.72℃ / min, 0.74℃ / min, 0.76℃ / min, 0.78℃ / min, or 0.8℃ / min.
[0042] For example, the second stage of constant temperature in the carbonization step can be 375℃, 376℃, 377℃, 378℃, 379℃, 380℃, 381℃, 382℃, 383℃, 384℃, or 385℃.
[0043] For example, the second isothermal time in the carbonization step can be 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3.0 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h, or 4 h.
[0044] For example, the heating rate in the third stage of the carbonization step can be 0.6℃ / min, 0.62℃ / min, 0.64℃ / min, 0.66℃ / min, 0.68℃ / min, 0.7℃ / min, 0.72℃ / min, 0.74℃ / min, 0.76℃ / min, 0.78℃ / min, or 0.8℃ / min.
[0045] For example, the third stage of the carbonization process can be at a constant temperature of 1150℃, 1160℃, 1170℃, 1180℃, 1190℃, 1200℃, 1210℃, 1220℃, 1230℃, 1240℃, or 1250℃.
[0046] For example, the third isothermal time in the carbonization step can be 9 h, 9.2 h, 9.4 h, 9.6 h, 9.8 h, 10 h, 10.2 h, 10.4 h, 10.6 h, 10.8 h, or 11 h.
[0047] And / or, the graphitization process includes: using an inert gas as a protective gas, heating the carbonized primary product to 2250-2350℃ at a rate of 1.4-1.6℃ / min and holding it at that temperature for 48-60 hours.
[0048] For example, the heating rate in the graphitization step can be 1.4℃ / min, 1.42℃ / min, 1.44℃ / min, 1.46℃ / min, 1.48℃ / min, 1.5℃ / min, 1.52℃ / min, 1.54℃ / min, 1.56℃ / min, 1.58℃ / min, or 1.6℃ / min.
[0049] For example, the isothermal temperature in the graphitization step can be 2250℃, 2260℃, 2270℃, 2280℃, 2290℃, 2300℃, 2310℃, 2320℃, 2330℃, 2340℃, or 2350℃.
[0050] For example, the isothermal time in the graphitization step can be 48 h, 49.2 h, 50.4 h, 51.6 h, 52.8 h, 54 h, 55.2 h, 56.4 h, 57.6 h, 58.8 h, or 60 h.
[0051] The present invention also provides a consumable for wafer manufacturing, comprising the graphite material described in any of the foregoing embodiments.
[0052] This invention also provides a method for screening graphite material consumables for wafer fabrication, wherein the graphite material has a photocurability coefficient of 0.03-0.15 cm⁻¹. 3If the graphite material is / g, then it is a qualified graphite material consumable for wafer manufacturing; the optical curvature coefficient of the graphite material is less than 0.03 cm⁻¹. 3 / g or greater than 0.15cm 3 If / g, then the graphite material is a substandard graphite material consumable for wafer manufacturing; wherein, the optical solidity coefficient = transmittance at a wavelength of 260nm × porosity / density.
[0053] In the current graphite material production process, the formula and process can only be adjusted based on experience, resulting in poor batch consistency, low repeatability, and difficulty in large-scale mass production, such as light transmittance behavior. This application ensures the uniformity and reliability of graphite products by screening the light-curing coefficient.
[0054] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0055] Example 1 This embodiment provides a method for preparing graphite material, specifically including the following steps: For the ingredients, weigh out 100 parts of pitch coke (Hebei Deri New Material Technology Co., Ltd., same manufacturer and model as in subsequent examples), 10 parts of microcrystalline wax powder (CAS: 8001-75-0), 7 parts of nano-sized hollow carbon spheres (particle size 20-500 nm, Xi'an Qiyue Biotechnology, same manufacturer and model as in subsequent examples), and 10 parts of phenolic resin (Jinan Shengquan Group Co., Ltd., carbon-containing and carbon resin, same manufacturer and model as in subsequent examples). Mix the weighed raw materials evenly to obtain a raw material mixture. Cold pressing: The raw material is cold pressed at room temperature and 35 MPa for 3 minutes to obtain the initial product. Heat treatment: Place the product in an oven and heat it to 138°C at a rate of 8°C / min, hold it at that temperature for 6 hours, and then cool it to room temperature. Carbonization involves transferring the heat-treated primary product to a carbonization furnace. Using argon as a protective gas, the heat-treated primary product is heated to 325℃ at a rate of 0.5℃ / min and held at that temperature for 2 hours. Then, the temperature is increased to 375℃ at a rate of 0.8℃ / min and held at that temperature for 4 hours. Finally, the temperature is increased to 1250℃ at a rate of 0.6℃ / min and held at that temperature for 9 hours to obtain the carbonized crude product. Graphitization: The crude product was transferred to a graphitization furnace, and argon was used as a protective gas. The temperature was increased to 2250℃ at a rate of 1.6℃ / min and held at that temperature for 60 hours to obtain the graphite material. SEM images are shown below. Figure 1 As shown.
[0056] Example 2 This embodiment provides a method for preparing graphite material, specifically including the following steps: For the ingredients, weigh out 100 parts of pitch coke, 11 parts of microcrystalline wax powder, 6 parts of nano-sized hollow carbon spheres, and 15 parts of phenolic resin. Mix the weighed ingredients evenly to obtain a mixture of ingredients. Cold pressing: The raw material is cold pressed at room temperature and 28 MPa for 3 minutes to obtain the initial product. Heat treatment: Place the product in an oven and heat it to 140℃ at a rate of 8℃ / min, hold it at that temperature for 5 hours, and then cool it to room temperature. Carbonization involves transferring the heat-treated primary product to a carbonization furnace. Using argon as a protective gas, the heat-treated primary product is heated to 320℃ at a rate of 0.6℃ / min and held at that temperature for 2-4 hours. Then, the temperature is increased to 380℃ at a rate of 0.7℃ / min and held at that temperature for 3 hours. Finally, the temperature is increased to 1200℃ at a rate of 0.7℃ / min and held at that temperature for 10 hours to obtain the carbonized crude product. Graphitization involves transferring the crude product to a graphitization furnace, using argon as a protective gas, and heating it to 2300℃ at a rate of 1.5℃ / min and holding it at that temperature for 54 hours to obtain the graphite material.
[0057] Example 3 This embodiment provides a method for preparing graphite material, specifically including the following steps: For the ingredients, weigh out 100 parts of pitch coke, 12 parts of microcrystalline wax powder, 5 parts of nano-sized hollow carbon spheres, and 20 parts of phenolic resin. Mix the weighed ingredients evenly to obtain a mixture of ingredients. Cold pressing: The raw material is cold pressed at room temperature and 15 MPa for 3 minutes to obtain the initial product. Heat treatment: Place the product in an oven and heat it to 142℃ at a rate of 8℃ / min, hold it at that temperature for 4 hours, and then cool it to room temperature. Carbonization involves transferring the heat-treated primary product to a carbonization furnace. Using argon as a protective gas, the heat-treated primary product is heated to 315℃ at a rate of 0.7℃ / min and held at that temperature for 4 hours. Then, the temperature is increased to 385℃ at a rate of 0.6℃ / min and held at that temperature for 2 hours. Finally, the temperature is increased to 1150℃ at a rate of 0.8℃ / min and held at that temperature for 11 hours to obtain the carbonized crude product. Graphitization: The crude product is transferred to a graphitization furnace, and argon is used as a protective gas. The temperature is increased to 2350℃ at 1.4℃ / min and held at that temperature for 48 hours to obtain the graphite material.
[0058] Comparative Example 1 This comparative example provides a method for preparing graphite material. The main difference from Example 1 is that the amount of microcrystalline wax powder weighed in the batching step is too small, only 8 parts.
[0059] Comparative Example 2 This comparative example provides a method for preparing graphite material. The main difference from Example 1 is that the amount of microcrystalline wax powder weighed in the batching step is too large, which is 15 parts.
[0060] Comparative Example 3 This comparative example provides a method for preparing graphite material. The main difference from Example 1 is that the mass of hollow carbon spheres weighed in the batching step is too small, only 2 parts.
[0061] Comparative Example 4 This comparative example provides a method for preparing graphite material. The main difference from Example 1 is that the mass of hollow carbon spheres weighed in the batching step is too large, consisting of 10 parts.
[0062] The transmittance, porosity, and density of the graphite materials prepared in the above embodiments and comparative examples were tested at a wavelength of 260 nm. The test methods and conditions are as follows, and the optical solidification coefficient was calculated based on the test results. The calculation results are shown in Table 1.
[0063] Test methods and conditions: Porosity, tested by mercury porosimetry, in accordance with GB / T 21650.1-2008.
[0064] Density, tested according to GB / T 24203-2009.
[0065] Transmittance at 260nm wavelength was measured using a UV-Vis-NIR spectrophotometer, model Shimadzu UV-3600i Plus, with a sample thickness of 2mm.
[0066] Optical solidity coefficient = transmittance at 260nm wavelength × porosity / density.
[0067] CV value: Each of the above embodiments and comparative examples was repeated 5 times to obtain 5 graphite material samples. The optical curing coefficient of each sample was tested and calculated. The standard deviation and average value of the optical curing coefficients of the 5 samples obtained in the same embodiment and comparative example were calculated, and the optical curing coefficient CV value was calculated, where CV value = (standard deviation ÷ average value) × 100%.
[0068] Table 1
[0069] Based on the above embodiments and comparative examples, and in conjunction with Table 1, it can be seen that: By limiting the optical solidity coefficient to the range of 0.03-0.15, the material simultaneously possesses suitable light transmittance (0.08-0.18), porosity (0.3-0.6), and density (0.1-1.0 g / cm³). 3 The data from Examples 1-3 are all within this range, indicating that the product was successfully prepared and performed well.
[0070] Limiting the optical solidity coefficient to the range of 0.03-0.15 ensures that the effective light transmission behavior per unit mass of material is stable and controllable, which is beneficial for graphite materials to have stable light transmission characteristics and is a prerequisite for improving the consistency of wafer fabrication.
[0071] In Table 1, the optical curing coefficients (CVs) of Examples 1-3 are 2.9%, 3.1%, and 3.0%, respectively. The optical curing coefficients of Comparative Examples 1 and 3 are less than 0.03, while those of Comparative Example 4 are greater than 0.15. Their CV values are much higher than those of Examples 1-3. The CV values of Comparative Examples 1, 3, and 4 reach 7.0%, 6.8%, and 7.1%, respectively, indicating that the graphite materials prepared by the scheme of this application have small batch-to-batch fluctuations, high consistency, and high stability.
[0072] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a graphite material, characterized in that, include: The raw material mixture is cold-pressed to obtain the initial product; By weight, the raw material mixture comprises the following components: 100 parts of pitch coke, 10-12 parts of microcrystalline wax powder, 5-7 parts of nano-sized hollow carbon spheres, and 10-20 parts of phenolic resin; the cold pressing pressure is 15-35 MPa. The primary product is subjected to heat treatment, carbonization, and graphitization sequentially to obtain the graphite material. The heat treatment includes heating the primary product to 138-142℃ at 7-9℃ / min and holding it at that temperature for 4-6 hours, then cooling it to 18-30℃. The carbonization includes: using an inert gas as a protective gas, heating the heat-treated primary product to 315-325℃ at 0.5-0.7℃ / min and holding it at that temperature for 2-4 hours; then heating it to 375-385℃ at 0.6-0.8℃ / min and holding it at that temperature for 2-4 hours; finally heating it to 1150-1250℃ at 0.6-0.8℃ / min and holding it at that temperature for 9-11 hours to obtain a carbonized crude product. The graphitization includes: using an inert gas as a protective gas, heating the carbonized primary product at 1.4-1.6℃ / min... Heat to 2250-2350℃ and maintain the temperature for 48-60 hours; The optical curvature coefficient of the graphite material is 0.03-0.15 cm⁻¹. 3 / g, where the optical solidification coefficient = transmittance at 260nm wavelength × porosity / density.
2. The method for preparing graphite material according to claim 1, characterized in that, The optical curvature coefficient of the graphite material is 0.04-0.12 cm⁻¹. 3 / g.
3. The method for preparing graphite material according to claim 1, characterized in that, The optical curvature of the graphite material is 0.04-0.05 cm⁻¹. 3 / g.
4. The method for preparing graphite material according to claim 1, characterized in that, The optical curvature coefficient of the graphite material is 0.05-0.07 cm⁻¹. 3 / g.
5. The method for preparing graphite material according to claim 1, characterized in that, The optical curvature coefficient of the graphite material is 0.10-0.12 cm⁻¹. 3 / g.
6. A consumable for wafer manufacturing, characterized in that, Includes the graphite material as described in any one of claims 1-5.
Citation Information
Patent Citations
Graphite material with high thermal conductivity
CN104725047A
Carbon graphite material and preparation method thereof
CN114920577A